Hoya imperialis Lindl. (Apocynaceae: Asclepiadaceae), a new record for Thailand - Sae Wai, Jarearnsak; Sridith, Kitichate; Thaithong, Obchant (Thai Forest Bulletin (Botany), 2014)
Hoya imperialis Lindl. is newly recorded for Thailand from Betong district in Yala province. The species is described and illustrated.